Inclusive Development through Providing Vertical Housing for Low Income Family in Yogyakarta Urban Areas - Rini Rachmawati; Charina Vertinia Budiarti; Diana Febrita; Estin Sulistyani (Forum Geografi, 2017)
Inclusive development is meant to accommodate the marginalised people, most of whom are the poor with the problem of fulfilling their need for housing. The government has tried hard to meet the need of housing by constructing rusunawa. This paper is aimed at describing the provision and uses of rusunawa, both in cities and peri-urban area by studying the cases in the City of Yogyakarta, Sleman Regency, and Bantul Regency. The study was conducted by doing observation and both structured and in-depth interviews. The research results show that rusunawa were viewed as one solution to help a low-income family in fulfilling their need for housing. In some cases in the City of Yogyakarta, rusunawa plays an essential role in preventing the settlement along both sides of rivers from becoming slum areas. Rusunawa in both Regencies of Sleman and Bantul is located near the city, so it is easy for the settlers to get to their workplace. The construction of rusunawa has also paid attention to the disabled by providing exceptional facilities. The same case is providing a playground for children and facilities for early education for young kids. However, there have not been special facilities for the elderly and pregnant women.